Diagnostic Accuracy of Ultrasound in Cholestatic Infants with Biliary Atresia - Hermis Arsena; Audric Kenny Tedja; Hesti Gunarti; Tiara Putri Leksono; Afina Azka Latifanisa Kuncoro; Adisrasti Rejeki Amaragati; Akhmad Makhmudi; Gunadi (AVES Yayincilik, 2024)
Objective: Biliary atresia (BA) is an obstructive cholangiopathy that involves the intrahepatic and extrahepatic bile ducts. Ultrasound (US) can aid in evaluation of the biliary system and be efficiently used in daily practice. However, most studies on US for diagnosing BA have been conducted in developed countries. Therefore, we have aimed to evaluate the diagnostic accuracy of US in BA in infants with cholestasis from a developing country. Materials and Methods: This retrospective study used data collected from our hospital medical records. The US findings were compared with the gold standard intraoperative or cholangiography findings. Results: Thirty-five BA patients (19 males and 16 females) and 36 controls (20 males and 16 females) were included in the study. Most of the patients (85.7%) were ≤ 6 months old. The absence of a gallbladder demonstrated 71.42% sensitivity (Sn), 91.67% specificity (Sp), 89.29% positive predictive value (PPV), 76.74% negative predictive value (NPV), 8.57 positive likelihood ratio (LR+), and 0.31 negative likelihood ratio (LR−) for diagnosing BA. The triangular cord sign demonstrated 14.28% Sn, 100% Sp, 100% PPV, 76.74% NPV, ∞ LR+, and 0.86 LR- for diagnosing BA. The combination of gallbladder absence and a positive triangular cord sign demonstrated 82.85% Sn, 91.67% Sp, 90.63% PPV, 84.61% NPV, 9.95 LR+, and 0.19 LR− for diagnosing BA. Conclusion: The diagnostic accuracy of US in BA is high, indicating that it can be the imaging tool of choice in infants with cholestasis. Ultrasound is safe and can be easily used in daily practice without the risk of radiation exposure.